2023
DOI: 10.3390/ijms24119151
|View full text |Cite
|
Sign up to set email alerts
|

FUNDC1: An Emerging Mitochondrial and MAMs Protein for Mitochondrial Quality Control in Heart Diseases

Xizhe Bai,
Zhe Zhang,
Xi Li
et al.

Abstract: Heart diseases (HDs) are the leading cause of mortality worldwide, with mitochondrial dysfunction being a significant factor in their development. The recently discovered mitophagy receptor, FUNDC1, plays a critical role in regulating the homeostasis of the Mitochondrial Quality Control (MQC) system and contributing to HDs. The phosphorylation of specific regions of FUNDC1 and varying levels of its expression have been shown to have diverse effects on cardiac injury. This review presents a comprehensive consol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 87 publications
(122 reference statements)
0
3
0
Order By: Relevance
“…Fundc1-triggered mitophagy has been shown to offer protection against ischemia-reperfusion (I/R) injury and Dox-induced cardiac dysfunction. 5557 Our data suggest that Fundc1-mediated mitophagy may be a potential mechanism through which Cyp1a inhibition mitigates Dox-induced cardiomyopathy. Wu et al previously reported that deficiency of Fundc1 in mice impairs heart function.…”
Section: Discussionmentioning
confidence: 81%
“…Fundc1-triggered mitophagy has been shown to offer protection against ischemia-reperfusion (I/R) injury and Dox-induced cardiac dysfunction. 5557 Our data suggest that Fundc1-mediated mitophagy may be a potential mechanism through which Cyp1a inhibition mitigates Dox-induced cardiomyopathy. Wu et al previously reported that deficiency of Fundc1 in mice impairs heart function.…”
Section: Discussionmentioning
confidence: 81%
“…The subsequent degradation of mitofusin stimulates mitochondrial fission and induces mitophagy [242]. PINK1/Parkin-independent pathways to induce mitophagy are reviewed in detail elsewhere [240,243,244].…”
Section: Pten-induced Putative Kinase 1 (Pink1)mentioning
confidence: 99%
“…Since MQC, i.e., the regulation and maintenance of mitochondrial homeostasis, is essential not only for the fine-tuning of cell energy production [115] but also for overall cellular health, mitochondrial dysfunction and inadequate QC inevitably lead to metabolic disorders in many pathological conditions [116,117]. Defective MQC has been associated with diseases of the heart [118], lung [119,120], and kidneys [121], and in neuronal and muscular disorders [122]. Further, the metabolic switch from ATP production by oxidative phosphorylation to aerobic glycolysis (the Warburg effect) is one of the underlining mechanisms of cancer cell proliferation, allowing transformed cells to adjust and grow in a poorly oxygenated milieu [123].…”
Section: Mitochondrial Dysfunctionmentioning
confidence: 99%